(untitled) (Scientific journal of the Fergana State University, 2023)
All over the world, interest in paraffin and ceresin is growing, as the areas of their application and processing are constantly expanding in order to obtain new types of polymeric and composite materials. Paraffin and ceresin are mainly used in medicine, paper industry, agriculture, electronics and other sectors of the economy. At the same time, the purity of paraffins and ceresins is considered one of the main requirements of the above-mentioned consumers, and therefore the development of an innovative technology for deep purification of paraffins is of priority importance. The article provides information about the developed combined technology for deep purification of paraffin on adsorbents from local raw materials. Scientific novelty of research -possible conditions for deep purification of paraffins, ceresins and their mixtures on the created dosing compositions have been developed; - developed technologies for receiving dispensers using clay minerals and a mechano-chemical activator, as well as for deep cleaning of paraffins, ceresins and their mixtures using; - developed technology of exposure in pilot production conditions for obtaining deeply purified paraffin for new purposes of their use.